Hubungan Kompetensi Kewirausahaan Dan Kinerja Usaha: Studi Empiris UMKM Di Kota Tarakan - Nurjannatul Hasanah; Mohamad Nur Utomo; Hariyadi Hamid (Management Insight: Jurnal Ilmiah Manajemen, 2018)
Entrepreneurial success is determined by the competencies of an entrepreneur and will directly affect the success of business performance. This study aims to examine empirically the influence of entrepreneurial competencies on business performance. Entrepreneurship competency is measured by 15 indicators (Ability to control risk, autonomy, Search for and analyze information, Communication, Dynamic, Build social networks, Change management, Initiatives, Innovation, Integrity, Leadership, Results-oriented, Negotiation, Problem solving and Responsibility ) While Business Performance is measured by 5 indicators (profit growth, sales growth, capital growth, efficiency and customer growth). The sample in this study was MSMEs in the city of Tarakan using a sample probability area sample method based on the sub -district area. The data analysis technique uses the PLS-SEM method with the WarpPls 6.0 application. The results of the study show that entrepreneurial competence has a positive impact on business performance. This study supports the RBV theory which states that a company's competitive advantage is generated from its unique resources.